Feasibility between Two Models for the Control of Fleet Idleness: RFID Antennas vs Electronic Fences (Telemetry) - Chaves, Andre Garofalo; De Lima, Romulo Guimaraes; Silva, Ricardo Moreira (International Journal of Supply Chain Management, 2018)
Optimizing the use of resources within organizations without decreasing the level of quality of service is a constant and recurring challenge in the daily life of professionals. In Group X, an electricity distribution company located in the Brazilian Northeast, fleet management is one of the priorities. This study compares the use of two tools to measure fleet idleness, RFID Antennas and electronic fences created from the Telemetry system. The process and cost of installation, scope, maintenance costs and results obtained were compared between the two tools. This comparison was used to analyze the feasibility of expanding the tools in Group X for newly acquired companies. Based on the results, it was concluded that the Telemetry system was economically and operationally the best option for Group X.